2020
DOI: 10.1016/j.ssci.2020.104985
|View full text |Cite
|
Sign up to set email alerts
|

How safe is it to shop? Estimating the amount of space needed to safely social distance in various retail environments

Abstract: Highlights We explore the problem of capacity for social distancing across various retail environments. We provide guidance to managers as lockdown eases and establishments are allowed to reopen. The paper identifies the minimum amount of space needed per person in different scenarios. We estimate the optimal capacity for retailers to provide a safe environment for shoppers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 28 publications
1
18
0
Order By: Relevance
“…Therefore, the finding confirms and supports H3 (b = 0.18, p = 0.00), H4 (b = 0.34, p = 0.00), H5 (b = 0.40, p = 0.00), and H6 (b = 0.70, p = 0.05). The result signifiedthat perceived usefulness has a significant and positive impact on user intention to use mobile payment.This finding is in agreement with the previous studies [23,67,68,[70][71][72], where it could be explained that the higher the use of mobile payment system, the greater the user intention is to use it.…”
Section: Structural Modelsupporting
confidence: 93%
See 1 more Smart Citation
“…Therefore, the finding confirms and supports H3 (b = 0.18, p = 0.00), H4 (b = 0.34, p = 0.00), H5 (b = 0.40, p = 0.00), and H6 (b = 0.70, p = 0.05). The result signifiedthat perceived usefulness has a significant and positive impact on user intention to use mobile payment.This finding is in agreement with the previous studies [23,67,68,[70][71][72], where it could be explained that the higher the use of mobile payment system, the greater the user intention is to use it.…”
Section: Structural Modelsupporting
confidence: 93%
“…The degree that consumers accept that online transactions by internet payment will provide valuable information, convenience in comparison to others, and speed up the shortcut purchase process [67]. In mobile payment systems, different studies demonstrated that a user realizes the highest level of usefulness when the consumer intends to use m-payment service [23,[67][68][69][70][71][72]. In the adoption of mobile payment technology, perceived usefulness is the most widely studied factor.…”
Section: Perceived Usefulnessmentioning
confidence: 99%
“…However, the current research has considered a similar approach as the studies conducted by Gössling and Scott [14] and Ntounis and Mumford [103], who proved that the tourist shopping as well as food places and services have been affected by COVID−19, but food service has been seriously affected due to limited liquidity, small profit margins [14], and COVID transmission through food [104]. In non-shopping malls, such as a night markets, the situation is more vulnerable, especially in Malaysia, because most of the vendors are categorised in the B40 (bottom 40% of people), where their incomes are under 3000 MYR (700 US Dollars) per month.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Yet, confusion about what steps have to be taken is hindering the efforts of retail traders, and there is an immediate necessity to comprehend how distancing can be secure. Ntounis, Mumford et al [ 33 ] estimated the amount of space needed to safely social distance in various retail environments when there are people present. The proposed method can work as a step forward in understanding the very practical problem of capacity, which can allow retail spaces to operate safely and minimise the risk of virus transmission.…”
Section: Discussionmentioning
confidence: 99%
“…In conjunction with the retail sector, the latest research of [ 32 ] argues that the willingness of shoppers to return to shopping depends on their feeling of safety, which is strongly related to measures like providing hand sanitiser, limiting the number of people in stores and monitoring social distancing. With the aim to solve the issue of social distancing [ 33 ], exploit theoretical knowledge in different areas of research such as crowd science [ 34 ] or operational research of ergonomics [ 35 ]. With this theoretical foundation, the researchers developed an extensive method to determine the minimum amount of space an individual needs for social distancing in closed and open commercial spaces.…”
Section: Literature Reviewmentioning
confidence: 99%